Acculturation in Islam: Han Kitab and Islam Nusantara - Anadza, Hirshi; Pasopati, Rommel Utungga (Journal of Integrative International Relations, 2019)
In China, Han Kitab is an example in how Chinese culture and Islam recognized each other. Ancient Chinese culture is not omitted but enriched by Islam. Confucianism and Islam are different in its each teaching but may crisscross philosophically. Both may come from different backgrounds but both teach people how to behave as individual and part of society. In Indonesia, Islam Nusantara is how Indonesian culture is understood through Islamic perspective. Islam which came later must face many ancient rituals or thoughts. It could not totally eliminate local culture but it can clear up bad aspect of local habits by teaching Islamic way of life. Both Han Kitab and Islam Nusantara shows that Islam did not come to apply such system by force, but it builds such apprehension through acculturation.